Preparation and characterization of polyaniline, cellulose triacetate and cellulose triacetatepolyaniline-lithium salt blend films / Faith Paujik - Paujik, Faith (Faculty of Applied Sciences, 2009)
A study is being done on polyaniline, cellulose triacetate and cellulose triacetatepolyaniline- lithium salt blend films. Polyaniline containing lithium salt is blended with cellulose triacetate to obtain both good physical and electrical properties. It was found that at 20% weight percentage salt, conductivity is the highest which is 2.829 x 10⁻⁶. This result agrees with Scanning Electron Microscopy (SEM) result which shows there is more conducting path in the film. As the addition of lithium salt increases, conductivity started to decrease due to formation of neutral ion pair thus reducing free mobile ions. The Fourier Transform Infrared Spectroscopy (FTIR) study shows that complexation between polyaniline and lithium salt occurs.